2020
DOI: 10.1080/17501229.2020.1714630
|View full text |Cite
|
Sign up to set email alerts
|

Learning beyond the classroom: students’ attitudes towards the integration of CLIL and museum-based pedagogies

Abstract: In the last two decades, several studies have reported on the benefits of Content and Language Integrated Learning (CLIL) on students' affective and cognitive gains. These studies, however, have mainly concentrated on the implementation of CLIL within the formal (school) context, with very little research on its impact in non-formal (out-of-school) contexts. Thus, the present article addresses this gap by describing an action research project aimed at understanding secondary school students' attitudes towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Such benefits, alongside challenges, have been investigated with young learners (e.g. Fazzi and Lasagabaster, 2020; Pérez Cañado, 2018) and higher education students (e.g. Aguilar and Muňoz, 2014; Vega and Moscoso, 2019).…”
Section: Clil and Clil Teacher Educationmentioning
confidence: 99%
“…Such benefits, alongside challenges, have been investigated with young learners (e.g. Fazzi and Lasagabaster, 2020; Pérez Cañado, 2018) and higher education students (e.g. Aguilar and Muňoz, 2014; Vega and Moscoso, 2019).…”
Section: Clil and Clil Teacher Educationmentioning
confidence: 99%
“…them more frequent abroad, 65,66,67 virtually, 68,69 in closed and isolated spaces 70,71 or in non-formal education 72 than in familiar and formal settings.…”
Section: Discussionmentioning
confidence: 99%
“…CLIL seems to be tremendously effective when applied in many European countries (e.g., Fazzi & Lasagabaster, 2021;Mahan, 2020;Pérez Cañado, 2020). However, in EFL contexts, the impact of CLIL does not seem to be that clear.…”
Section: Discussionmentioning
confidence: 99%
“…CLIL has been adopted worldwide as a successful teaching approach that promotes more motivated and sustained learning attainment (Marsh, 2000). A wealth of studies adopting CLIL principles have been conducted (e.g., Fan & Lo, 2016;Fazzi & Lasagabaster, 2021;Kalay, 2021;Navarro-Guzman et al, 2021;Mahan, 2020;Pérez Cañado, 2020;Thuy & Nguyen, 2016;Yang, 2015).These previous CLIL empirical studies have congruently demonstrated its positive impacts on encouraging students to concurrently learn the content subjects and the target language across disciplines (e.g., psychology, engineering, physical education, mathematics), at a number of educational establishments (e.g., high schools, vocational colleges, universities), in different levels of the educational paradigm (i.e., young learners, teenagers, and adults), and in a variety of academic contexts and linguistic backgrounds (e.g., Taiwan, Vietnam, and many European countries).…”
Section: Introductionmentioning
confidence: 99%